A reinforced coconut char, jute and glass fibers composite material mechanical effects compared by using taguchi method and analysis (Anova) technique - Kumar, J. G. K.; Babu, Dr. R. Venkatesh; Murugan, M. Arul (International Journal of Engineering and Technology, 2018)
This research work explains the different mechanical effects of natural fiber composites to increase its strength and they were reinforced with different reinforcements. The matrix is considered as natural fiber matrix composites with coconut char; Jute and glass fiber      composite materials were taken and give special properties for different applications in automobiles. Natural fiber composites have different advanced applications in current engineering materials. Hence the special properties like high strength, greater flexibility and abundantly available properties. With the help of different combination and proportions these materials were reinforced with different combinational materials were obtained for testing and selection of best combination material. The general properties for any material like mechanical properties of different reinforcements with different samples were tested and results were analyzed with the help of ANOVA and signal to noise ratio were found out by using MINITAB 18 Statistical software and results were compared.